Three new species of oribatid mites of the family Punctoribatidae (Acari, Oribatida) from alpine bogs of New Zealand - Ermilov, Sergey G.; Minor, Maria A. (Zootaxa, 2016)
Three new species of oribatid mites of the family Punctoribatidae (Acari, Oribatida) are described from alpine bogs of the Central Otago region in the South Island of New Zealand. Macrogena hexasetosa sp. nov. is morphologically most similar to M. brevisensilla Ermilov & Minor, 2015, however, it differs from the latter by larger body size, the presence of six pairs of genital setae, notogastral and ano-adanal setae of medium size, setiform rostral setae, narrower tutorial cusps, the absence of antero-ventral teeth on genua I, II and femora II, and by the absence of striae on the subcapitular mentum. Porallozetes badamdorji sp. nov. differs from the type species—P. dispar (Hammer, 1973)—by larger body length, the presence of interlamellar setae, short and clavate bothridial setae, anterior notogastral margin, notogastral setae of medium size, semi-oval dorsophragmata, and by the position of notogastral porose areas A2 posteriorly to A1. Safrobates gerdi sp. nov. differs from the type species—S. miniporus Mahunka, 1989—by larger body size, the presence of setiform rostral setae, and by notogastral setae of medium length. Porallozetes and Safrobates are recorded in New Zealand for the first time. Generic diagnoses for Macrogena, Porallozetes and Safrobates are given.